2023
DOI: 10.3389/fphar.2023.1281090
|View full text |Cite
|
Sign up to set email alerts
|

Berberine-microbiota interplay: orchestrating gut health through modulation of the gut microbiota and metabolic transformation into bioactive metabolites

Tessa Dehau,
Marc Cherlet,
Siska Croubels
et al.

Abstract: Berberine is an isoquinoline alkaloid found in plants. It presents a wide range of pharmacological activities, including anti-inflammatory and antioxidant properties, despite a low oral bioavailability. Growing evidence suggests that the gut microbiota is the target of berberine, and that the microbiota metabolizes berberine to active metabolites, although little evidence exists in the specific species involved in its therapeutic effects. This study was performed to detail the bidirectional interactions of ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Previous research has suggested that the gut microbiome plays a significant role in the metabolism and potentiation of biological effects of berberine in humans [ 17 , 21 ]. One proposed mechanism for the blood glucose lowering effects of berberine is through its modulation of the gut microbiota [ 52 ], as demonstrated in animal models of diabetes [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that the gut microbiome plays a significant role in the metabolism and potentiation of biological effects of berberine in humans [ 17 , 21 ]. One proposed mechanism for the blood glucose lowering effects of berberine is through its modulation of the gut microbiota [ 52 ], as demonstrated in animal models of diabetes [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…While berberine has demonstrated the ability to improve the metabolic syndrome through modulation of gut microbiota and enhancement of the integrity of the intestinal barrier [ 16 , 19 , 20 ], the pharmacological activity of berberine is also mediated by its metabolites, which play crucial roles both in direct biological activities and in their interactions with the gut microbiome [ 21 ]. Notable among these metabolites are jatrorrhizine, columbamine, demethyleneberberine, berberrubine, and thalifendine, each contributing to the pharmacological effects of berberine through distinct mechanisms [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the potentially beneficial bacteria Blautia plays an important role in maintaining intestinal homeostasis and preventing inflammation ( Liu et al, 2021 ), and involved in bile acid metabolism due to its BSH activity ( Song et al, 2019 ). A recent study revealed that Blautia may be a key bacterium involved in BBR metabolism by conversion of BBR into a more readily absorbed methylated metabolite ( Dehau et al, 2023b ). These results confirmed the efficacy of BBR in ameliorating the gut microbiota imbalance induced by ETEC and enhancing the abundance of beneficial bacteria in piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that BBR exhibits low absorption into the bloodstream, with a significant accumulation in the intestines where it exerts its pharmacological effects locally. BBR affects the gut-liver axis at several interrelated levels, including modulation of the gut microbiota structure, alteration of gut microbe-derived metabolites, etc., which reduces • Increases the ability of short-chain fatty acids (SCFAs) to produce bacteria Frontiers in Pharmacology frontiersin.org microbial exposure and the pro-inflammatory environment of the liver and modulates liver metabolism (Peng et al, 2019;Dehau et al, 2023;Zhu and Li, 2023). Zhang et al (2015) collected feces from C57 mice fed a high-fat diet (HFD) for 10 weeks and collected feces from non-alcoholic hepatitis model mice fed BBR (100 mg/kg body weight) for eight consecutive weeks and performed 16sRNA sequencing.…”
Section: Alkaloidmentioning
confidence: 99%